Seven Years of Membranes: Feature Paper 2017 - Spas D. Kolev (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
For the last seven years, Membranes has provided an outstanding platform for the publication of articles at the forefront of research in the areas of membrane fabrication, characterization and application. This Special Issue, entitled "Seven Years of Membranes: Feature Paper 2017," celebrates this achievement. The articles included in this Special Issue, written by prominent researchers in the field, provide an authoritative and up-to-date account of the advances in membrane science and technology. They describe new methods for the fabrication of organic, inorganic and mixed matrix membranes and their utilization in improving the efficiency of membrane-based separation processes, such as membrane distillation, nanofiltration, ultrafiltration, reverse osmosis, and gas permeation. A number of articles are focused on water treatment, which, because of its significance to sustainable development, is one of the main areas of membrane research and application. These articles report novel techniques for the clean-up of contaminated waters, and the desalination of industrial effluents, brackish water and seawater.